Prevalence and correlates of periodic limb movements in OSA and the effect of CPAP therapy. (28th April 2020) - Budhiraja, Rohit; Javaheri, Sogol; Pavlova, Milena K.; Epstein, Lawrence J.; Omobomi, Olabimpe; Quan, Stuart F.
Abstract : Objective: We sought to assess the prevalence, correlates, and consequences of periodic limb movements of sleep (PLMS) in persons with obstructive sleep apnea (OSA) and the effect (worsening or improvement) of continuous positive airway pressure (CPAP) therapy on PLMS in a large prospective multicenter randomized controlled trial. Methods: We performed retrospective analyses of data from the Apnea Positive Pressure Long-term Efficacy Study, a prospective multicenter randomized controlled trial. A total of 1, 105 persons with OSA enrolled in this study underwent a polysomnographic investigation at baseline, another one for CPAP titration, and another study 6 months after randomization to either active CPAP or sham CPAP. Results: Of all participants, 19.7% had PLM index (PLMI) ≥10/hour, 14.8% had PLMI ≥15/hour, 12.1% had PLMI ≥20/hour, 9.3% had PLMI ≥25/hour, and 7.5% had PLMI ≥30/hour. The odds of having a PLMI ≥10 were higher in older participants (odds ratio [OR] 1.03, p < 0.001), men (OR 1.63. p = 0.007), those using antidepressants (OR 1.48. p = 0.048), and those with higher caffeine use (OR 1.01, p = 0.04). After controlling for OSA and depression, PLMS were associated with increased sleep latency, reduced sleep efficiency, and reduced total sleep time. No significant relationships were noted between PLMS frequency and subjective sleepiness (Epworth Sleepiness Scale score) or objective sleepiness (Maintenance of Wakefulness Test). There was no differential effect of CPAP in comparison to sham CPAP on PLMS after 6 months of therapy. Conclusions: PLMS are common in patients with OSA and are associated with a significant reduction in sleep quality over and above that conferred by OSA. Treatment with CPAP does not affect the severity of PLMS.